Mechanism of action of microRNA166 on nitric oxide in alfalfa (Medicago sativa L.) under drought stress - Bochuang Wei; Yizhen Wang; Qian Ruan; Xiaolin Zhu; Xian Wang; Tianjie Wang; Ying Zhao; Xiaohong Wei (BMC Genomics, 2024)
Abstract Background Alfalfa is a perennial forage crop of high importance, but its cultivation is often affected by drought stress. Currently, the investigation of drought-related small RNAs is a popular research topic to uncover plant drought resistance mechanisms. Among these small RNAs, microRNA166 (miR166) is associated with drought in numerous plant species. Initial small RNA sequencing studies have shown that miR166 is highly responsive to exogenous nitric oxide (NO) and drought. Therefore, analyzing the expression of Msa-miR166 under nitric oxide and drought treatment is significant. Result Bioinformatics analysis revealed that the miR166 family is widely distributed among plants, ranging from mosses to eudicots, with significant distribution differences between species. The evolutionary degree of Msa-miR166s is highly similar to that of Barrel medic (Medicago truncatula) and Soybean (Glycine max), but significantly different from the model plant Arabidopsis (Arabidopsis thaliana). It is suggested that there are no significant differences in miR166s within the species, and members of Msa-miR166s can form a typical stem-loop. The lowest level of exogenous nitric oxide was observed in Msa-miR166s under drought stress, followed by individual drought, and the highest level was observed after removing endogenous nitric oxide. Conclusion In response to short-term drought, Msa-miR166s down-regulate expression in alfalfa (Medicago sativa L.). Exogenous nitric oxide can reduce the expression of Msa-miR166s in response to short-term drought. These findings suggest that Msa-miR166e-5p is responsive to environmental changes. The expression levels of target genes showed an opposite trend to Msa-miR166s, verifying the accuracy of Degradome sequencing in the early stage. This suggests that alfalfa experiences drought stress when regulated by exogenous nitric oxide, targeting HD ZIP-III, FRI, and CoA ligase genes. Additionally, the expression of Msa-miR166s in response to drought stress varies between leaves and roots, indicating spatiotemporal specificity.